Anterior laryngeal electrodes for recurrent laryngeal nerve monitoring during thyroid and parathyroid surgery: New expanded options for neural monitoring. (12th November 2018) - Liddy, Whitney; Lawson, Bradley R.; Barber, Samuel R.; Kamani, Dipti; Shama, Mohamed; Soylu, Selen; Wu, Che Wei; Chiang, Feng‐Yu; Scharpf, Joseph; Barczynski, Marcin; Dralle, Henning; Van Slycke, Sam; et al.
Abstract : Objectives/Hypothesis: Intraoperative neural monitoring is a useful adjunct for the laryngeal nerve function assessment during thyroid and parathyroid surgery. Typically, monitoring is performed by measurement of electromyographic responses recorded by endotracheal tube (ETT) surface electrodes. Tube position alterations during surgery can cause displacement of the electrodes relative to the vocal cords, leading to false positive loss of signal. Numerous reports have denoted monitoring equipment–related issues, especially endotracheal tube displacement, as the dominant source of false positive error. The false positive error may result in inappropriate decisions by the surgeon. This study tests the hypothesis that anterior laryngeal electrodes (ALEs) can help reduce this error. Placement of ALEs directly onto the thyroid cartilage represent an adjunctive and possible alternative method to standard ETT surface electrodes. Study Design: Retrospective review. Methods: Fifteen consecutive patients undergoing thyroid and parathyroid surgery with intraoperative neuromonitoring using both ETT electrodes and ALEs were studied. Data collected included site of neural stimulation, laterality, and electromyographic parameters. Results: With vagal and recurrent laryngeal nerve stimulation, the ALEs recorded mean vocalis muscle waveform amplitude within 83% of that recorded with standard ETT electrodes. The latency measurements with the anterior laryngeal and endotracheal electrodes were similar, with both electrodes recording significantly longer latency for the left vagus nerve as compared to the right vagus nerve. With superior laryngeal nerve stimulation, the ALEs recorded a 800% greater mean amplitude than the ETT electrodes. The ALEs demonstrated similar sensitivity to stimulation at low current as ETT electrodes and provided stable intraoperative monitoring information. Conclusions: Compared to ETT surface electrodes, the ALEs provide similar and stable electromyographic responses with equal sensitivity for recording evoked responses during neural monitoring in thyroid and parathyroid surgery. The ALEs offer significantly more robust monitoring of the external branch of the superior laryngeal nerve. Furthermore, ALEs are contained within the operative field, are totally surgeon controlled, and are unaffected by the potential vicissitudes of ETT position during surgery. Level of Evidence: 4 Laryngoscope, 128:2910–2915, 2018